EFFECT OF DIFFERENT EXTENDERS ON HYPO-OSMOTIC SWELLING OF DOG SEMEN PRESERVED AT 5° C - DAS, ARUNODAY; BISWAS, R K; DEKA, B C (The Indian Journal of Animal Reproduction, 2023)
The objective of the present study was to evaluate the preservability of different extenders for dog semen on the basis of hypo-osmotic swelling test (HOST). Semen samples from three Labrador Retriever (LR) dogs were collected by digital manipulation method at weekly intervals. The first and second fractions of the ejaculates were collected combinedly in a single collection cup. The semen samples· were then extended @ 1 :4 in Tris-Egg Yolk- Citric Acid-Glucose (TEYCAG), Tris-Egg Yolk- Citric Acid-Fructose (TEYCAF) and Egg Yolk-Citrate-Glycine-Glucose (EYCGG) extenders by split sample technique and preserved at 5° C. The preserved semen was evaluated for HOST-reacted sperm at 24, 48, 72, 96 and 120 hours of preservation. The mean incidence of HOST- reacted sperm was 93.44 ± 1.92, 92.20 ± 1.72 and 85.65 ± 3.01 ; 87.99 ± 4.35, 85.56 ± 3.82 and 75.34 ± 6.86; 85.03 ± 4.23, 82.25 ± 4.32 and 68.88 ± 7.46; 82.20 ± 4.42, 78.75 ± 5.17 and 59.33 ± 5.10; and 79.51 ± 4.25, 70.00 ± 3.63 and 52.50 ± 3.71 per cent in TEYCAG, TEYCAF and EYCGG extenders at 24, 48, 72, 96 and 120 hours of preservation respectively. Analysis of variance revealed that the mean incidence of HOST-reacted sperm differed significantly (P<0.01) between extenders and between preservation periods. But the interaction between extender and preservation period was not significant. The mean percentage of HOST-reacted sperm was significantly (P<0.05) higher in TEYCAG and TEYCAF extenders from that in EYCGG extender irrespective of hour of preservation. The incidence of HOSTreacted spermduring 48 to 120 hours of preservation decreased significantly (P<0.05) from that at 24 hours of preservation irrespective of extender. It was significantly (P<0.05) lower at 96 and 120 hours as compared to that at 48 hours, and at 120 hours than at 72 hours of preservation irrespective of extender. Per cent HOSTreacted spermatozoa did not differ significantly between TEYCAG and TEYCAF extenders irrespective of preservation period which might suggest that the two extenders were equally efficacious in providing functional integrity of the plasma membrane of LR dog spermatozoa during preservation.